The impact of after-school activities to enhance students’ academic performance in Vocational High School in Indonesia - Lambok Hermanto Sihombing (International Journal of Education and Learning, 2025)
After-school activities (ASA), also known as extracurricular activities, can be found in various forms at all academic levels. These activities could include English Club, sports, debate, or drama. They have become an essential component of school life for students. In order to comprehend this effect, the author intends to describe how extracurricular activities were used as touchpoints to enhance students' academic performance. The focus of the study was 500 students of Vocational High School in Bekasi, Indonesia. Specifically, this study utilized a mixed research approach. There were two instruments used in this study; a student survey and student reflections. The findings demonstrated that after-school activities affect the students’ academic performance especially in speaking skills. They also showed their improvement in self-esteem, critical thinking, and discipline.